Product Differentiation and Market Segmentation as Alternative Marketing Strategies - Smith, Wendell R. (Journal of Marketing, 1956)
URING the decade of the 1930's, the work of Robinson and Chamberlin resulted in a revitalization of economic theory. While classical and neoclassical theory provided a useful framework for economic analysis, the theories of perfect competition and pure monopoly had become inadequate as explanations of the contemporary business scene. The theory of perfect competition assumes homogeneity among the components of both the demand and supply sides of the market, but diversity or heterogeneity had come to be the rule rather than the exception. This analysis reviews major marketing strategy alternatives that are available to planners and merchandisers of products in an environment characterized by imperfect competition.